Incidence of farrowing assistance and neonatal challenges in hyperprolific sows: Insights from a field study - S. Blim; D. Lehn; T. Scheu; C. Koch; G. Thaller; K. Failing; H. Bostedt (Theriogenology, 2026)

The role of submarine volcanism in atmospheric chemistry - M. Colombier; M. Bonifacie; M. Brenna; A. Burke; C. Cimarelli; S.J. Cronin; P. Delmelle; D.B. Dingwell; K-U. Hess; M. Huebsch; T. Kula; F. Latu’ila; et al. (Earth and Planetary Science Letters, 2025)

MeMoVolc report on classification and dynamics of volcanic explosive eruptions - C. Bonadonna; R. Cioni; A. Costa; T. Druitt; J. Phillips; L. Pioli; D. Andronico; A. Harris; S. Scollo; O. Bachmann; G. Bagheri; S. Biass; et al. (Bulletin of Volcanology, 2016)

Sediment transport dynamics near a river inflow in a large alpine lake - K. R. Scheu; D. A. Fong; S. G. Monismith; O. B. Fringer (Limnology and Oceanography, 2015)
Sediment dynamics were investigated in Lake Maggiore, Italy, with field observations from October to mid‐December 2012. Three moorings were deployed in Pallanza Bay, a small embayment on the western side of the lake near the Toce River inflow, to measure temperature and currents throughout the water column and suspended sediment concentration (SSC) was estimated with acoustic instrumentation. River intrusions are shown to dominate observed SSC, although a small amount of sediment resuspension was observed at the site of the shallowest mooring during a large wind event that produced strong upwelling of the thermocline followed by downwelling. Although vertical turbulent sediment flux is typically assumed to indicate resuspension and the upward transport of sediment ( ), downward turbulent sediment flux was observed ( ) near the bed during the largest observed intrusion event. The downward turbulent sediment flux significantly contributes to net deposition rates, which are one order of magnitude larger than rates of erosion measured during the two major events observed. Horizontal transport of sediment occurs in vertically confined layers due to buoyancy‐driven intrusions. Beneath the intrusions, sediment settles out of the water column at settling rates that appear to be constant with depth based on acoustic Doppler current profiler backscatter measurements. The effective settling velocities needed to produce the observed vertical transport of SSC during an inflow intrusion are one order of magnitude larger than those due to the Stokes settling velocity ( ) alone. Particle flocculation and possible convective instabilities may play a role in generating the large observed effective settling rates.

The influence of fertilizer addition, cutting frequency and herbicide application on soil organisms in grassland - K. Lemanski; S. Scheu (Biology and Fertility of Soils, 2015)

Effects of prey quality and predator body size on prey DNA detection success in a centipede predator - B. Eitzinger; E. M. Unger; M. Traugott; S. Scheu (Molecular Ecology, 2014)
Predator body size and prey quality are important factors driving prey choice and consumption rates. Both factors might affect prey detection success in PCR ‐based gut content analysis, potentially resulting in over‐ or underestimation of feeding rates. Experimental evidence, however, is scarce. We examined how body size and prey quality affect prey DNA detection success in centipede predators. Due to metabolic rates increasing with body size, we hypothesized that prey DNA detection intervals will be shorter in large predators than in smaller ones. Moreover, we hypothesized that prey detection intervals of high‐quality prey, defined by low carbon‐to‐nitrogen ratio will be shorter than in low‐quality prey due to faster assimilation. Small, medium and large individuals of centipedes L ithobius spp. ( L ithobiidae, C hilopoda) were fed C ollembola and allowed to digest prey for up to 168 h post‐feeding. To test our second hypothesis, medium‐sized lithobiids were fed with either D iptera or L umbricidae. No significant differences in 50% prey DNA detection success time intervals for a 272‐bp prey DNA fragment were found between the predator size groups, indicating that body size does not affect prey DNA detection success. Post‐feeding detection intervals were significantly shorter in Lumbricidae and Diptera compared to Collembola prey, apparently supporting the second hypothesis. However, sensitivity of diagnostic PCR differed between prey types, and quantitative PCR revealed that concentration of targeted DNA varied significantly between prey types. This suggests that both DNA concentration and assay sensitivity need to be considered when assessing prey quality effects on prey DNA detection success.

Mechanisms linking plant community properties to soil aggregate stability in an experimental grassland plant diversity gradient - G. Pérès; D. Cluzeau; S. Menasseri; J. F. Soussana; H. Bessler; C. Engels; M. Habekost; G. Gleixner; A. Weigelt; W. W. Weisser; S. Scheu; N. Eisenhauer (Plant and Soil, 2013)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Magmatic architecture of dome-building eruptions at Volcán de Colima, Mexico - Yan Lavallée; N. R. Varley; M. A. Alatorre-Ibargüengoitia; K.-U. Hess; U. Kueppers; S. Mueller; D. Richard; B. Scheu; O. Spieler; D. B. Dingwell (Bulletin of Volcanology, 2012)

Divergent composition but similar function of soil food webs of individual plants: plant species and community effects - T. M. Bezemer; M. T. Fountain; J. M. Barea; S. Christensen; S. C. Dekker; H. Duyts; R. van Hal; J. A. Harvey; K. Hedlund; M. Maraun; J. Mikola; A. G. Mladenov; et al. (Ecology, 2010)
Soils are extremely rich in biodiversity, and soil organisms play pivotal roles in supporting terrestrial life, but the role that individual plants and plant communities play in influencing the diversity and functioning of soil food webs remains highly debated. Plants, as primary producers and providers of resources to the soil food web, are of vital importance for the composition, structure, and functioning of soil communities. However, whether natural soil food webs that are completely open to immigration and emigration differ underneath individual plants remains unknown. In a biodiversity restoration experiment we first compared the soil nematode communities of 228 individual plants belonging to eight herbaceous species. We included grass, leguminous, and non‐leguminous species. Each individual plant grew intermingled with other species, but all plant species had a different nematode community. Moreover, nematode communities were more similar when plant individuals were growing in the same as compared to different plant communities, and these effects were most apparent for the groups of bacterivorous, carnivorous, and omnivorous nematodes. Subsequently, we analyzed the composition, structure, and functioning of the complete soil food webs of 58 individual plants, belonging to two of the plant species, Lotus corniculatus (Fabaceae) and Plantago lanceolata (Plantaginaceae). We isolated and identified more than 150 taxa/groups of soil organisms. The soil community composition and structure of the entire food webs were influenced both by the species identity of the plant individual and the surrounding plant community. Unexpectedly, plant identity had the strongest effects on decomposing soil organisms, widely believed to be generalist feeders. In contrast, quantitative food web modeling showed that the composition of the plant community influenced nitrogen mineralization under individual plants, but that plant species identity did not affect nitrogen or carbon mineralization or food web stability. Hence, the composition and structure of entire soil food webs vary at the scale of individual plants and are strongly influenced by the species identity of the plant. However, the ecosystem functions these food webs provide are determined by the identity of the entire plant community.

Soil bacteria and protozoa affect root branching via effects on the auxin and cytokinin balance in plants - K. Krome; K. Rosenberg; C. Dickler; K. Kreuzer; J. Ludwig-Müller; C. Ullrich-Eberius; S. Scheu; M. Bonkowski (Plant and Soil, 2010)

Plant diversity effects on soil microorganisms support the singular hypothesis - N. Eisenhauer; H. Beßler; C. Engels; G. Gleixner; M. Habekost; A. Milcu; S. Partsch; A. C. W. Sabais; C. Scherber; S. Steinbeiss; A. Weigelt; W. W. Weisser; et al. (Ecology, 2010)
The global decline in biodiversity has generated concern over the consequences for ecosystem functioning and services. Although ecosystem functions driven by soil microorganisms such as plant productivity, decomposition, and nutrient cycling are of particular importance, interrelationships between plant diversity and soil microorganisms are poorly understood. We analyzed the response of soil microorganisms to variations in plant species richness (1–60) and plant functional group richness (1–4) in an experimental grassland system over a period of six years. Major abiotic and biotic factors were considered for exploring the mechanisms responsible for diversity effects. Further, microbial growth characteristics were assessed following the addition of macronutrients. Effects of plant diversity on soil microorganisms were most pronounced in the most diverse plant communities though differences only became established after a time lag of four years. Differences in microbial growth characteristics indicate successional changes from a disturbed (zymogeneous) to an established (autochthonous) microbial community four years after establishment of the experiment. Supporting the singular hypothesis for plant diversity, the results suggest that plant species are unique, each contributing to the functioning of the belowground system. The results reinforce the need for long‐term biodiversity experiments to fully appreciate consequences of current biodiversity loss for ecosystem functioning.

Influence of the Cooling Rate on the Mechanical Properties of a Hot-work Tool Steel - S. Mayer; C. Scheu; H. Leitner; H. Clemens; I. Siller (BHM Berg- und Hüttenmännische Monatshefte, 2007)

The soil food web of two beech forests ( Fagus sylvatica ) of contrasting humus type: stable isotope analysis of a macro- and a mesofauna-dominated community - S. Scheu; M. Falca (Oecologia, 2000)

Effects of litter (beech and stinging nettle) and earthworms (Octolasion lacteum) on carbon and nutrient cycling in beech forests on a basalt-limestone gradient: A laboratory experiment - S. Scheu (Biology and Fertility of Soils, 1997)